2013
DOI: 10.1104/pp.112.212407
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Copper Transport Protein COPT2 Participates in the Cross Talk between Iron Deficiency Responses and Low-Phosphate Signaling    

Abstract: Copper and iron are essential micronutrients for most living organisms because they participate as cofactors in biological processes, including respiration, photosynthesis, and oxidative stress protection. In many eukaryotic organisms, including yeast (Saccharomyces cerevisiae) and mammals, copper and iron homeostases are highly interconnected; yet, such interdependence is not well established in higher plants. Here, we propose that COPT2, a high-affinity copper transport protein, functions under copper and ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 72 publications
(90 reference statements)
9
134
0
Order By: Relevance
“…In addition, there are numerous works that show similarities between Fe and P deficiency responses, both in the type of responses and in their regulation and signaling. As several works have shown, a consequence of this relationship is the existence of induction of P deficiency responses by Fe deficiency and vice versa [2,4,[54][55][56]103]. This is logical if one considers that there are hormones, such as ethylene, involved in the activation of responses to both deficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are numerous works that show similarities between Fe and P deficiency responses, both in the type of responses and in their regulation and signaling. As several works have shown, a consequence of this relationship is the existence of induction of P deficiency responses by Fe deficiency and vice versa [2,4,[54][55][56]103]. This is logical if one considers that there are hormones, such as ethylene, involved in the activation of responses to both deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, it has been found that Fe deficiency induces the expression of P-related genes, that P deficiency induces the expression of Fe-related genes, and that both deficiencies induce the expression of ethylene-related genes [2,4,[54][55][56][57]. In addition, increased accumulation of Fe in leaves under P deficiency and of P under Fe deficiency has been found [14,37,56,[58][59][60][61][62].…”
Section: Fe and P Nutrition In Dicot Plantsmentioning
confidence: 99%
“…Furthermore, analysis of the COPT1, COPT2 and COPT6 promoter regions reveals multiple putative light and circadian cis-regulatory elements. 9,17,18 Some of these motifs are involved in phytochrome regulation of gene expression, 19 which corroborates the reduction of COPT2 transcript in the phy mutants. 15 Such cis-responsive elements could also participate in the regulation of the transcriptional factor SPL7, as they are found in its promoter (Fig.…”
Section: Plasma Membrane High Affinity Copper Transport Is Under Lighmentioning
confidence: 71%
“…8 Among them, COPT2 is the most highly expressed in young and adult tissues. 9 Cu uptake depends on both its availability in the apoplast and the density of Cu transporter proteins at the plasma membrane. 10 Under deficiency, the predominant strategy for Cu acquisition consists in a mechanism of reduction of Cu 2C to Cu C and subsequent Cu C uptake.…”
Section: Plasma Membrane Copts and Copper Transportmentioning
confidence: 99%
“…This outlook paper focuses on our contribution to characterizing the function and regulation of the different members of the conserved CTR/COPT family of high-affinity Cu transporters in the model plant Arabidopsis thaliana. [6,12,13,[46][47][48]. We observed that, with the exception of COPT4, the ectopic expression of all the Arabidopsis COPT family members expressed in yeast Cu transport mutants stimulates Cu uptake and accumulation [12,13,49].…”
Section: Introductionmentioning
confidence: 94%